Structure Community of Gastropods and Bivalves in Sabang Coastal - Chitra Octavina; Muhammad Irham; Dwi Zhahira Feriska (Jurnal Moluska Indonesia, 2023)
The wealth of marine life in the waters of Sabang City is very diverse that inhabits these waters. One organism or biota that is known to have an important role, both ecologically and environmentally, is thegroup of oluska from class Gastropods and bivalves. The purpose of the study is to determine the structure of the community through the formula approach of density, distribution patterns, diversity, uniformity, and dominance. Determination of location using pupossive sampling, sampling is carried out in two stages, namely taking aquatic parameters and sampling Gastropoda and Bivalves. The results of research at three observation stations in the Sabang water area which coincided on the coast of Anoi Itam, and Lhok Weng waters, found 19 species of Gastropda consisting of 10 families and 2 species of Bivalves consisting of 2 families. The highest gastropod density is found at station II of 8 ind/m2. The distribution pattern of 10 species is clustered and 9 species are uniform. The diversity value (H') of high criteria ranges from 1.14 – 1.40, the uniformity value (E) is balanced ranging from 0.63 – 0.81, the dominance value (C) ranges from 0.39 – 0.53. The highest density of Bivalves is found at station II at 0.69 ind/m2. The distribution pattern of 2 species is uniform. The diversity value (H') of the low category ranges from 0 - 0.09, the uniformity value (E) is unbalanced ranges from 0 - 0.07, and the dominance value (C) ranges from 0 - 0.95. The structure of the Gastropoda and Bivalve Community in Sabang Waters is in stable condition because there is no species that dominates the most